New mythological paradigm and the modern humanities. (Herald of Journalism, 2016)
The paper defines a new national scientific paradigm of literary studies - the problem of analyzing works of art as «a typical mythological system» provides foreign and domestic theoretical research in the field of mythology and literature.
Keywords: mythology; Serikbol Kondybai; myth; literature; mythological thinking; initiation; mythological school; folklore; mythical time; the mythic consciousness.